Gastric outlet obstruction by polypoid tumors - Herwig Cerwenka, (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Cerwenka H. Gastric outlet obstruction by polypoid tumors. Turk J Gastroenterol 2018; 29: 243-4.